Elaboração de iogurte com adição de farinha de yacon - Pizetta, Leticia Calvi (2013)
Yacon (Smallanthus sonchifolius) is originally from Andes but it has currently been produced in other countries, as Brazil. The root of yacon contains from 10% to 14% of dry matter and that content corresponds to 90% of carbohydrates, most of which (40%-70%) is fructo-oligosaccharides (FOS). FOS withstand temperatures around 140 oC, and pH above 3. For that reasons yacon can be used as source of FOS and can stand different treatments, such as the production of flour, which can be added to other products such as yogurt. Yogurt is the product of pasteurized milk fermentation by Streptococcus salivarius ssp. thermophilus e Lactobacillus delbrueckii ssp. bulgaricus. The objective of this research was to evaluate the effect of yacon flour addition on physico-chemical and sensory characteristics of yogurt. It were prepared yogurt with addition of 3,54% of yacon flour and yogurt without addition of yacon flour, used as control. Concerning yacon flour, it were quantified the levels of FOS and total dry matter (TDM) and its pH were determined. As to the yogurt, it were evaluated the physico-chemical aspects of TDM, ash, carbohydrate, protein, fat, titratable acidity, pH and syneresis. The values of pH and syneresis were determined every 7 days for a period of 28 days. Sensory acceptance was also evaluated through the attributes aroma, texture, flavor, overall impression and purchase intent. A questionnaire was administered in order to gather information on age, gender, income level, knowledge of prebiotic foods, yacon and yogurt consumption. The results showed significant difference (p<0,05) between yogurt types for total dry matter, ash, carbohydrante, pH and titratable acidity. The yogurt with addition of yacon flour had 20.55% TDM, 0.94% ash, 12.95% carbohydrate, pH 4.79 and 81.72oD titratable acidity, while the control product showed 18.84% TDM, 0.85% ash, 11.29% carbohydrate, pH 4.88 and 75.55oD titratable acidity. The sensory acceptance results showed that the addition of yacon flour affected yogurt appearance, texture and overall impression. The yogurt with addition of yacon flour achieved acceptance means between the hedonic terms indifferent and slightly liked on the scale. The control product achieved means between the hedonic terms slightly liked and liked a lot . The addition of yacon flour to yogurt is technologically feasible, as the yogurt showed acceptable physico-chemical and sensory characteristics